Recurrent Intracerebral Hemorrhage as a Result of Cerebral Amyloid Angiopathy - Kurniawan, Mohammad; Lestari, Dhara Ayu; Harris, Salim; Rasyid, Al; Mesiano, Taufik; Hidayat, Rakhmad (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2023)
Stroke is a major health problem in the world with high mortality dan morbidity rate. Hemorrhagic stroke is a type of stroke with a high mortality rate. One of the most common causes of hemorrhagic stroke in elderly is cerebral amyloid angiopathy. We present a case of recurrent hemorrhagic stroke with clinical manifestations of extremity weakness and seizure. Radiological imaging showed a lobar hemorrhage. Referring to the Boston criteria, based on the results of clinical evaluation and imaging, the patient was diagnosed with intracerebral hemorrhage et causa probable CAA without pathologic feature was established. Patients were treated with antihypertensive medicine for blood pressure control and steroid as anti-inflammatory agents with a good clinical and functional outcome.